Directional Control of Light with Nanoantennas (Advanced Optical Materials 1/2021). Issue 1 (4th January 2021) - Li, Nannan; Lai, Yunhe; Lam, Shiu Hei; Bai, Haoyuan; Shao, Lei; Wang, Jianfang
Abstract : To overcome the diffraction limit of electromagnetic waves, plasmonic and dielectric nanoantennas have been developed for manipulating the direction of light at nanoscale. The cover shows various types of nanoantennas made of different materials and in different architectures for directional light scattering and emission. They include V‐antennas, Yagi–Uda nanoantennas, metal nanowires, dielectric nanoparticles and bimetallic heterodimers. These nanoantennas are discussed in the review (article number 2001081 ) by Jianfang Wang and co‐workers, and they are expected to find useful applications in ultrasmall optical devices and nanocircuits in the future.